Desenvolvimento de método para análise de especiação de arsênio em derivados líquidos de arroz - Rosa, Francisco Cunha da (2018)
From the discovery of intolerances related to bovine milk and wheat, there is a growing demand for derived products from rice, such as milk, beer, sake, vinegar, among others. However, these products are potential holders of high arsenic concentrations, since many studies report that rice has large amounts of this element when compared to other foods. In this sense, the laws regulating these products are restricted to setting only limits for total As content, without considering the fact that there are large differences in toxicity among the known species of this element. The inorganic forms, As (III) and As (V), are up to 100 times more toxic than organics, such as DMA and MMA, commonly detected in rice. Faced with this, the simple determination of total As may not be enough, putting many humans at risk. It is therefore very important to provide more complete information on the As species concentration present in these derived products, which can be obtained from the speciation analysis. However, for this purpose the species must be kept in their original form, which requires great attention in terms of sample preparation. Therefore, it is necessary to employ milder methods, such as extractions, which are relatively time consuming and error prone by the number of steps involved. Thus, in order to meet this demand, we proposed the development of simpler and organic solvent-free methods, aiming the As speciation analysis by LC-ICP-MS in rice milk, beer, sake and rice vinegar. In this way, we evaluated the simple dilution of the samples, the heating for evaporation of the sample matrix, the samples freeze-drying to remove the matrix and a new technique called electromembrane extraction (EME). Also, parameters such as salt type, concentration, flow rate and pH of mobile phase were evaluated, aiming at the most appropriate conditions for determining the species As(III), As(V), MMA and DMA. The results were obtained from a comprehensive chromatographic condition and demonstrated that the simple dilution of the samples is satisfactory for As speciation analysis with a good accuracy level, from 80 to 120%, according to the recovery tests, and by comparison of the species sum with the total As concentration (t-test, with confidence interval greater than 95%) obtained by ICP-MS, after microwave assisted wet digestion (MAD). The rice milks and sake were those with the highest concentrations of total As (above 10 μg L-1). There was a predominance of inorganic species (approximately 50%), with exception of sake, where DMA predominates.